A factor analysis of characterization of “Politician” criteria by different generations in Mongolia - Gantuya, Ariunsan; Oyunsuren, Jargalsaikhan (Proceedings of the Mongolian Academy of Sciences, 2019)
Based on intergeneration theories, 2721 randomly sampled pollees are classified into 4 generations; namely Gen Z, Gen Y, Gen X and Gen BB. This paper aims to identify the difference between Mongolian generations, especially on subjective criteria to assess politicians. Based on the statistical result of factor analysis, 20 criteria are classified into 5 factors. KMO measurements above .800 and absolute significance value above .30 is used to set the boundaries for criteria grouped in one category and overlapping criteria are examined with ground justifications. Public perception of potential political representatives is researched among each generation, and commonality and discrepancies among generations are explained with quantitative verifications in the following paper. Statistics results reveal that there are common factors between Gen Z and Y, in which they perceive the factors such as the qualification and the public skills in a similar manner. Also, older generations including Gen X and BB have uniform understanding of education and political experience of politicians.